Anti-breast cancer effects of phytochemicals: primary, secondary, and tertiary care - Mazurakova, Alena; Koklesova, Lenka; Samec, Marek; Kudela, Erik; Kajo, Karol; Skuciova, Veronika; Csizmár, Sandra Hurta; Mestanova, Veronika; Pec, Martin; Adamkov, Marian; Al-Ishaq, Raghad Khalid; Smejkal, Karel; et al. (The EPMA journal, 2022)
Breast cancer incidence is actually the highest one among all cancers. Overall breast cancer management is associated with challenges considering risk assessment and predictive diagnostics, targeted prevention of metastatic disease, appropriate treatment options, and cost-effectiveness of approaches applied. Accumulated research evidence indicates promising anti-cancer effects of phytochemicals protecting cells against malignant transformation, inhibiting carcinogenesis and metastatic spread, supporting immune system and increasing effectiveness of conventional anti-cancer therapies, among others. Molecular and sub-/cellular mechanisms are highly complex affecting several pathways considered potent targets for advanced diagnostics and cost-effective treatments. Demonstrated anti-cancer affects, therefore, are clinically relevant for improving individual outcomes and might be applicable to the primary (protection against initial cancer development), secondary (protection against potential metastatic disease development), and tertiary (towards cascading complications) care. However, a detailed data analysis is essential to adapt treatment algorithms to individuals' and patients' needs. Consequently, advanced concepts of patient stratification, predictive diagnostics, targeted prevention, and treatments tailored to the individualized patient profile are instrumental for the cost-effective application of natural anti-cancer substances to improve overall breast cancer management benefiting affected individuals and the society at large.
Keywords: Breast cancer; Evidence-based research data; Treated cancer; Plants; Translational research; Primary secondary tertiary care; Molecular patterns; Phytochemicals; Individualized patient profiling; Cost-effective disease management; Predictive Preventive Personalized Medicine (PPPM/3PM); Improved individual outcomes; Stroke; Health risk assessment; Food; COVID-19; Modifiable risk factors